Academic Degrees: Beginning and Evolution - Mendoza Arana, Pedro (2000)
University, as an institution, appears in the XII Century, under two models: Parisian, where professors get together, and Bolognian, where students hired professor. The Parisian Model prevailed. From an organizational point of view, these Universities were guilds of professors, where the student was in training. These groups of professors started to require certain formalities for group admission. In this context, Master and Doctor academic degrees were pre-requisites for a specific profession: University Professor.However, this profession was possible in such a time. Currently, the density of knowledge makes the mastery of a condition necessary but not sufficient for this profession. I propose that the Academic Degree of Master has lost its original specificity of being oriented towards the training of University Professors, and is now socially requested as a general training to become an expert in a certain area of knowledge. Similary, requeriments for University teaching must include Master Degree but also advanced training in the sciences and methods of learning.